Engineering Performance of Asphalt Concrete by Marshall Test Using Different Reclaimed Asphalt Pavement Content - นกแก้ว, นิรชร (Srinakharinwirot University Engineering Journal, 2018)
This article aims to study the performance of asphalt concrete by Marshall Test using different reclaimed asphalt pavement (RAP) content. The experimental design detailed in this study included the use of one limestone aggregate source, no separation of RAP such as 10, 20, 30, 40, 50, 60 and 70 percent by mass of aggregate, asphalt cement (AC 60-70) at 5 percent by mass of aggregate. The research methodology used Marshall Test and binder course 19.0 mm in laboratory conditions. The study found that when using the amount of no separation of RAP in the range of 10 to 40 percent by mass of aggregate had job mix formula properties to meet the requirements of Asphalt Hot-Mix Recycling. The study found that RAP had a indirect tensile strength of 579.4 to 953.7 kPa, a resilient modulus of 1,242.0 to 1,504.1 kPa, static creep of 0.4935 to 0.9938 percent and dynamic creep of 3,870 to 4,774 microstrain.